El conquistador conquistado Álvar Núnez Cabeza de Vaca y la conquistada conquistadora Sor Juana Inés de la Cruz - Rodríguez Díaz del Real, Alejandro (Ars et humanitas, 2017)
Starting from two recent critical publications against the fatalism of the traditional discourse of the (anti-Spanish) Black Legend, which do not pretend to be revisionist but instead point out certain positive aspects to the conquest of the Americas, the article contrasts two works that illustrate the permeability of two minds who wanted to open up to diversity: Álvar Núnez Cabeza de Vaca with his Shipwrecks (Naufragios) on the one hand, and Sor Juana Inés de la Cruz with his Allegorical Neptune (Neptuno alegórico) on the other. Only half a century after the discovery of America, and in the exact year of the New Laws of Charles V, which reflect the spirit of Las Casas critics and a defence of the Indian that later landed in the anti-Spanish Black Legend, Cabeza de Vaca presents a case of self-discovery as a fascinated conqueror who ends up conquered by the very environment that he is supposed to dominate; by a world that is too different and mysterious not to arouse his curiosity. The article contrasts this adventure of empathy and knowledge towards the other with an original work by Sor Juana Inés de la Cruz, Neptuno alegórico (1680), which represents another kind of journey, more a literary than autobiographical one, of the American world towards a Baroque or European "otherness". In spite of the considerable time that separates each case, and of the logical and predictable divergences in terms of literary genre, both works are united by a willingness to be carried away by cultural spheres and aesthetic guidelines that are far from the known world, doing what today we would call "leaving one's comfort zone", but achieving an enrichment of the authors- own lived and creative experience, as well as the literary horizon of the reader.
Keywords: barok; Cruz, Sor Juana Ines de la; indigenizem; latinskoameriške književnosti; Núnez Cabeza de Vaca, Alvar